Digital Signal Processing (with CD) - S Poornachandra (Tata McGraw Hill Education, 2010)
Designed for a first course in Digital Signal Processing, this book covers major topics like Discrete Fourier Transform Fast Fourier Transform), design of digital filters, effect of finite word length and multirate signal processing. Written in a clear style, the book provides lot of solved problems, illustrations and flow graphs that will facilitate easy learning of the subject. Key Features Comprehensive coverage of FIR and IIR filters. Simple and student-friendly presentation. Appropriate mathematical analysis to understand concepts. New chapter on digital signal processor. A tutorial on MATLAB with solved. More than 250 solved problems and numerous exercises for practice Summary at the end-of each chapter.